Cardiac development long non-coding RNA (CARDEL) is activated during human heart development and contributes to cardiac specification and homeostasis - Pereira, Isabela T. (2024)
Data Availability Statement: RNA-Seq data generated in this study have been deposited in the NCBI Sequence Read Archive under accession number PRJNA926378 and are publicly available as of the date of publication. RNA-seq data of in vitro cardiac differentiation was previously generated by our group [17] and is available at NCBI Sequence Read Archive, accession number SRP150416. RNA-seq data heart tissues were acquired from European Nucleotide Archive (ENA) (http://www.ebi.ac.uk/ena, accessed on 25 May 2022). Accession numbers for adult heart tissue data: ERR315356, ERR315430, ERR315367 and ERR315331. Project number for fetal heart tissue data: PRJEB27811 [18].